Strategi Penyajian Berita oleh Jurnalis detikSumut di Media Detikcom - Asri Widyanti; Defhany .; Nurhawati Simamora (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
The rapid growth of digital media in Indonesia has created a complex challenge: while 77% of Indonesians actively consume online news, 42% still fall prey to hoax content (SAIL-CSIS, 2024). Despite the proliferation of regional digital news portals, there remains a research gap in understanding the operational strategies of local journalists on national platforms such as detikSumut in maintaining news quality amid the disruption of digital information. This study aims to identify and analyze the strategies employed by digital journalists at detikSumut in presenting online news on the detikcom platform. Employing a qualitative descriptive method, data were gathered through observation, in-depth interviews with five informants selected via purposive sampling (two digital journalists, one editorial assistant, and two public audience members), and documentation. Data analysis followed the Miles and Huberman model comprising data reduction, display, and conclusion, validated through source triangulation. The findings reveal four key strategies: (1) proactive topic planning each evening through synchronization of national and local North Sumatera issues; (2) multi-layered verification with credible institutional sources using the 5W+1H framework; (3) application of the inverted pyramid writing model with straight-to-the-point leads; and (4) close editorial collaboration ensuring adherence to journalistic ethics. These strategies enable detikSumut to maintain speed, accuracy, and local relevance in the digital era.